EVALUASI PROGRAM INOVASI DALAM PENERAPAN PENDEKATAN CIPP DI DI SEKOLAH DASAR NEGERI - Mutia, Ananta Dwi; Bernadette, Amanda Devania; Maqfiroh, Aulia Faridhatul; Raudha, Avrillika Najla; Kazandra, Bella; Sumarsono, Raden Bambang; Setiawan, Wildan Darma (STKIP Pesisir Selatan, 2026)
This study aims to evaluate the innovation program in the implementation of School-Based Management (SBM) at SDN Pandanwangi 01 Malang using the CIPP (Context, Input, Process, Product) evaluation model. The research approach used was qualitative with a case study method through observation, in-depth interviews with the principal, and documentation analysis. The results showed that the implementation of SBM in this school was based on the need to improve the quality of learning, strengthen character, and involve the school community. Input analysis showed the support of competent human resources, transparent funding through BOS and parental contributions, and creative utilization of infrastructure, although limited. The program implementation process was systematic through daily habits, Teacher Cafe forums, Thematic Friday activities, and external partnerships that strengthened curriculum and literacy innovation. The resulting products include increased discipline, environmental character, student literacy, and more inclusive access to learning. Overall, the implementation of SBM at SDN Pandanwangi 01 has proven effective in improving the quality of education, although strengthening more operational evaluation instruments is still needed so that continuous improvements can be carried out in a measurable manner.